Optimization of PCR Analysis Based on Start Codon Targeted Markers (SCoT Markers) for Identification of Genetic Variation of Seaweed from Central Sulawesi - Santoso, Tri Joko; Husni, Ali; Nugroho, Kristianto; Ya’la, Zakirah Raihani; Dewi, Triyani; Marhawati, Marhawati; Maemunah, Maemunah; Rosyida, Eka; Ndobe, Samliok (Journal La Lifesci, 2024)
Seaweed is a fishery commodity that has high economic value because it contains carrageenan which can be used in the pharmaceutical, food, cosmetics, and industrial fields. Central Sulawesi Province is the second largest seaweed producer in Indonesia after South Sulawesi Province. The genetic diversity of seaweed in Central Sulawesi has not been studied much. Therefore, molecular-based characterization activities to identify the genetic variation of seaweed in the province are urgently needed. The purpose of the study was to optimize PCR techniques based on targeted start codon markers (SCoT markers) to identify the genetic diversity of seaweed accessions from Central Sulawesi Province. The results showed that the parameters for seaweed PCR amplification have been optimized. Of the fifteen SCoT primers, 10 of them can work to amplify seaweed DNA collected from several regions in Central Sulawesi. This is shown by the production of PCR result amplicons. PCR results also indicate polymorphism from the seaweed samples tested, although some seaweed samples have not been successfully amplified. The parameters of the PCR technique still need to be improved, especially the concentration of DNA prints, so that valid PCR results will be obtained for use in identifying seaweed genetic diversity.